Negative Representations of Byzantine Princesses in Serbian Medieval Hagiographies - Krneta, Mila (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
If we analyse all examples where Byzantine princesses were mentioned in Serbian hagiographies, we could reach certain conclusions.The performances of the Byzantine princesses in the above mentioned lives are not uniform and the descriptions of their characters ranged from extremely positive to extremely negative. If we look closely at their mentions, it is observed that the description of each of them was intended to tell us more directly about the hero of this life: to portray him as a good diplomat, martyr, strong ruler and knight, or a weak man; then to provide appropriate moral instruction to readers; or to convey with a conveyed meaning a picture of the relationship between Byzantium and Serbia at the time it describes. In a negative light are depicted princess Anna Angel in Theodosius' Life of Saint Sava and Simonides in the Life of Stefan Decanski by Grigory Camblak. The performances of these two Byzantine princess are full of stereotypes and do not represent realistic descriptions of their personalities.
Keywords: hagiographies; women; trope; cunning; malicious; shameless